BRG1 attenuates colonic inflammation and tumorigenesis through autophagy-dependent oxidative stress sequestration - Min Liu (Nature Portfolio, 2019)
Dysfunctional autophagy induces inflammation that contributes to tumorigenesis. Here, the authors show that loss of BRG1 impairs autophagy and enhances reactive oxygen species production to disrupt intestinal barrier integrity, leading to spontaneous colitis and subsequent colorectal cancer development.